2019
DOI: 10.6004/jnccn.2019.7369
|View full text |Cite
|
Sign up to set email alerts
|

Testicular Cancer Survivorship

Abstract: Testicular cancer (TC) is the most common cancer among men aged 18 to 39 years. It is highly curable, with a 10-year relative survival approaching 95% due to effective cisplatin-based chemotherapy. Given the increasing incidence of TC and improved survival, TC survivors (TCS) now account for approximately 4% of all US male cancer survivors. They have also become a valuable cohort for adult-onset cancer survivorship research, given their prolonged survival. Commensurately, long-term treatment-related complicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 120 publications
0
54
0
1
Order By: Relevance
“…An increased risk of second malignancies in cancer survivors has been associated with previous exposure to CT and/or RT [61]. In GCT survivors, an increased risk of various second tumours, comprising haematological, gastro-intestinal (GI), and urologic malignancies is already well established [62][63][64][65][66][67][68]. A significant 3-fold risk of leukaemia, after a median latency of 5 years, was reported in an international population-based study of 18,576 TGCTs who underwent pelvic RT [69], and both cisplatin and etoposide have been associated with elevated risks of secondary leukaemia in survivors [69,70].…”
Section: General Overviewmentioning
confidence: 99%
“…An increased risk of second malignancies in cancer survivors has been associated with previous exposure to CT and/or RT [61]. In GCT survivors, an increased risk of various second tumours, comprising haematological, gastro-intestinal (GI), and urologic malignancies is already well established [62][63][64][65][66][67][68]. A significant 3-fold risk of leukaemia, after a median latency of 5 years, was reported in an international population-based study of 18,576 TGCTs who underwent pelvic RT [69], and both cisplatin and etoposide have been associated with elevated risks of secondary leukaemia in survivors [69,70].…”
Section: General Overviewmentioning
confidence: 99%
“… 18 In contrast, a Serbian study found that 12% of TC survivors experienced mild or moderate depression. 19 The National Comprehensive Cancer Network 20 indicated that there is no sufficient evidence to argue that TC survivors experience higher levels of depression than the general population.…”
Section: Introductionmentioning
confidence: 99%
“…Testicular germ cell tumors (TGCTs) are among the most frequent solid neoplasms in young‐adult Caucasian men, and incidence is increasing worldwide due to life‐style changes [1]. These patients show an overall good prognosis (especially due to high efficacy of platinum‐based chemotherapy) and often become long‐term cancer survivors [2]. Nonetheless, a substantial number of patients are overtreated, receiving adjuvant treatment although they would never endure disease recurrence.…”
Section: Introductionmentioning
confidence: 99%